The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2010
DOI: 10.1109/aim.2010.5695944
|View full text |Cite
|
Sign up to set email alerts
|

Principles of motion control of bacterial micro-robots using oxygen gradients

Abstract: We introduce a method of motion control for bacterial microrobots using oxygen gradients. The bacteria (magnetotactic coccus strain MC-1) have a strong preference for a particular oxygen concentration and reverse swimming direction in order to remain at that oxygen concentration. At the same time, MC-1 consume oxygen, changing the dynamics of the system. We propose that we can use this behavior to passively control the motion of bands of MC-1 by carefully setting oxygen inputs. Mode of operation is introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Oxygen can be a strong attractant for some microorganisms. Shechter et al [ 37 ] demonstrated that bacteria actively moved via oxygen gradient in the medium from the lowest concentration to the highest. It is necessary to mention that magnetotactic bacteria were used in this study, which provides an opportunity to investigate joint control by using magnetic field and oxygen concentration gradients.…”
Section: Current Approaches In the Microbial Cell Based Microrobots D...mentioning
confidence: 99%
“…Oxygen can be a strong attractant for some microorganisms. Shechter et al [ 37 ] demonstrated that bacteria actively moved via oxygen gradient in the medium from the lowest concentration to the highest. It is necessary to mention that magnetotactic bacteria were used in this study, which provides an opportunity to investigate joint control by using magnetic field and oxygen concentration gradients.…”
Section: Current Approaches In the Microbial Cell Based Microrobots D...mentioning
confidence: 99%
“…Many bio-inspired swimming robots rely on tethered power supplies or onboard batteries, which are not suitable for microrobots [6,7]. A number of actuation methods for micron-sized devices can be found in literature, including the use of real bacteria to move micro-objects [8][9][10] or the use of chemically fuelled devices [11][12][13]. Both of these methods provide onboard actuation but are limited in the types of environments that can be employed.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled swimming of bio-inspired robots is crucial to high precision in-vivo and in-vitro applications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%